Aplicação do método Kaizen e 5S ao Laboratório de Fluidodinâmica e Particulado da UFPA - SOUZA, Isaac França (2022)
Modern industry as we know it developed mostly after World War II. We had large-scale production systems before the WWI period, but concepts of quality, customer satisfaction, low cost, economy, etc. were not addressed in industry as factors for profit maximization and customer welfare. Today we have a continuous search for quality by industry and service providers. The beginnings of this search were given by the Japanese, and the influences of North American researchers, who ended up adopting and creating many of the quality systems we know today. This was a determining factor for Japan to rise as an economic power, considering its post-war state. The Japanese economic success was such that their industryattracted the atten tion of many countries, being the target of studies and examples for other countries to adopt the same strategies as the Japanese. This allowed a more accurate perception of the need for quality tools, since through these tools the Japanese industry grew delivering quality products and influencing foreign industries. The industries work with quality tools always aiming to maximize the quality of their products, thinking about the customers. The present work seeks to apply the quality tools in the Fluid Dynamics and Particulates Laboratory, a place of research for the most diverse companies and for academic development. With situations that are totally inappropriate to the solutions proposed by an engineering company. The proposal for implementation starts from a previous analysis of the local conditions a nd an evaluation of the laboratory concepts in the 5S and Kaizen frameworks in order to raise graphical data for comparison after implementation. The methodology applied was based on data obtained through a questionnaire containing questions to analyze the conditions of the laboratory, the purpose was to search for data that corroborated the real conditions of the place of analysis. With this, it was possible to hold lectures with all employees, which was passed to them the philosophy of the 5S and Kaizen program, elucidating the proposals that the tool proposes to solve with its application. The implementation was in the scope of the norms of the 5S program, in order to apply each concept of the program in the laboratory. Thus, it is evident, given the laboratory's proposals, the need to implement NR's, which was done, taking into account those NR's likely to be necessary in the laboratory. At the end, it was possible to verify an improvement in the concepts of quality and safety. These improvements were regarding the organization of the laboratory, cleanliness, order of the tools and equipment used by employees, as well as the safety of the same, due to the implementation of warning stickers, the preparation of a risk map, as well as the risks at the workplace. This allowed for greater safety for employees, organization of the laboratory premises, learning for employees, and the improvement of what was applied.